Sociocultural Interface Between ESL Teachers' Beliefs and Technology-Enhanced Classroom Practices in Ekiti State, Nigeria - DEJI-AFUYE, Oladunni Olufunso; DEJI-AFUYE, Opeyeoluwa Adesina (Universitas Jambi, Magister Program of English Education Department, 2025)
This study explores the intersection of sociocultural factors, English as a Second Language (ESL) teachers' beliefs, and technology-enhanced classroom practices in secondary schools in Ekiti State, Nigeria. Grounded in the Technology Acceptance Model (TAM), this research investigates how teachers' perceived usefulness, ease of use, and attitude towards technology integration influence their classroom practices. Using a mixed-methods approach, this study integrates data from classroom observations and semi-structured interviews with 10 ESL teachers. The findings reveal significant relationships between teachers' beliefs, sociocultural factors, and technology adoption. The findings indicate that teachers' beliefs about technology-enhanced learning, cultural values, and school policies impact technology integration. TAM's efficacy in explaining the adoption of technology by ESL teachers is supported. The study highlights the importance of considering sociocultural factors in technology-enhanced ESL education. Implications for educational practice, policy, and future research are discussed. Specifically, the study recommends contextualized teacher training programs, infrastructure development, responsive technology-based resources, and policy reforms to support effective technology integration in classroom practices.